2007
DOI: 10.1016/j.bone.2007.04.182
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal ethanol exposure disrupts the histological stages of fetal bone development

Abstract: Maternal ethanol intake during pregnancy results in impairments in general growth and skeletal development in the offspring. We have previously shown that ethanol retards skeletal ossification at doses lower than those that affect growth. Moreover skeletal sites vary in their sensitivity to ethanol effects, with more severe effects occurring in bones that undergo a greater proportion of their development in utero. Taken together, these data suggest that ethanol has specific effects on bone development, and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 34 publications
3
30
1
1
Order By: Relevance
“…bone formation process, and reduce bone mineral content and bone density (Shankar et al, 2008). In early developmental stage, PEE restricts endochondral ossification process by inhibiting the development of resting zone in growth plate and by extending the length of HZ, thereby retards long bone development (Snow and Keiver, 2007). Consistent with this, we also found that PEE retards long bone development with enlarged HZ and shortened length of POC in fetus.…”
Section: Pee Retards Endochondral Ossification In Fetal Long Bonesupporting
confidence: 68%
See 1 more Smart Citation
“…bone formation process, and reduce bone mineral content and bone density (Shankar et al, 2008). In early developmental stage, PEE restricts endochondral ossification process by inhibiting the development of resting zone in growth plate and by extending the length of HZ, thereby retards long bone development (Snow and Keiver, 2007). Consistent with this, we also found that PEE retards long bone development with enlarged HZ and shortened length of POC in fetus.…”
Section: Pee Retards Endochondral Ossification In Fetal Long Bonesupporting
confidence: 68%
“…Previous studies in our laboratory showed that birth weight of PEE offspring was significantly lower than the control, while the IUGR rate was significantly higher, due to a high level of maternal glucocorticoid induced by PEE (Liang et al, 2011;Shen et al, 2014;Ni et al, 2015). Other studies also show that PEE could significantly reduce fetal body weight and body length as well as suppress longitudinal growth of fetal bone, and affect fetal bone mineralization (Simpson et A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 6 / 31 al., 2005;Snow and Keiver, 2007). The intrauterine growth deficits may affect postnatal bone development and persist into adulthood (Lanham et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Undernourished pups, compared to the control group, showed adverse outcomes as demonstrated by several factors, including femur length (-47%; P < 0.001) and bone calcium (-67%; P < 0.001) and phosphorus (-46%; P < 0.001) contents. Using a different approach, Snow and Keiver [16] investigated the infl uence of maternal ethanol intake on offspring bone formation. In this Canadian study, 37 rats were divided into three groups.…”
Section: Animal Modelsmentioning
confidence: 99%
“…In a related study, Snow and Keiver [18] reported that prenatal ethanol exposure has effect on the resting zone of the developing bone indicating that earlier stages of bone development may also be disrupted. The decrease in the length of the resting zone increased the length of the hypertrophic zone and enlarged, which was consistent with an effect of ethanol on the later stages of bone development.…”
Section: Discussionmentioning
confidence: 99%